2013
DOI: 10.1155/2013/905942
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Characterisation of Pitting Corrosion on Sensitized Austenitic Stainless Steel by Digital Image Analysis

Abstract: Pit morphology on sensitized 310S stainless steel has been studied using an image processing method based on reflected light microscopy. Salt Spray (fog) test has been used to induce the pitting corrosion. Morphological pits characters do not depend on sensitization heat treatments applied here. Nucleation rates and growth may be associated with quantity and distribution of chromium carbides. This being so, condition I (heating up to 1065 ∘ C during 1 h and air cooling) and condition II (heating up to 1065 ∘ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The different phases presence in deposits depends on the Ni and Zn relative amount in bath [16]. In this study, the authors confirmed that deposits obtained from solutions containing a Ni 2+ /Zn 2+ ratio of 0. mate conversion [18]. Images of untreated Zn-Ni electrodeposits, Figure 2, and chromatized alloy, Figure 3, resulted in very distinct superficial aspects.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The different phases presence in deposits depends on the Ni and Zn relative amount in bath [16]. In this study, the authors confirmed that deposits obtained from solutions containing a Ni 2+ /Zn 2+ ratio of 0. mate conversion [18]. Images of untreated Zn-Ni electrodeposits, Figure 2, and chromatized alloy, Figure 3, resulted in very distinct superficial aspects.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%